Strengthening Religious Moderation for High School and Vocational School Spiritual Activists in Semarang City - Bisri, Kasan; Azizah, Nurul; Rahman, Luthfi; Falah, M. Fajrul; Haqiqi, Abdurrahman Raden Aji (Indonesian Journal of Islamic Education Studies (IJIES), 2023)
Religious intolerance phenomenon in the school environment is still common. It is a severe problem that must be addressed and a solution found together so that it does not become a source of radical religious movements. Strengthening religious moderation for Rohis (Islamic spirituality) in schools is very important as a provision for them in society and the state. This activity aims to enhance the attitude of religious moderation and determine the level of Islamic understanding of spiritual activists in high schools and vocational schools in Semarang, Central Java. This article uses descriptive quantitative methods. The data collection technique uses a questionnaire as a survey, distributed as a Google Form. The data analysis technique uses descriptive analysis techniques. The results show that strengthening Rohis religious moderation for High and Vocational Schools in Semarang City was conducted through workshops and visits. The percentage of spiritual activists' level of understanding of Islam, which is based on the principle of moderation of the 25 respondents who have a moderate sense or moderate sense, is calculated to be 12%, and those who have behavior above a moderate mind, moderate behavior, is estimated to be 88%. This activity implies the need for follow-up activities from the Rohis extracurricular for each high and vocational school to further optimize the extra program with actions that uphold the value of religious moderation.